Engaging Farmers in Climate Change Adaptation Planning: Assessing Inte rcropping as a Means to Support Farm Adaptive Capacity - Himanen, Sari J.; Mäkinen, Hanna; Rimhanen, Karoliina; Savikko, Riitta (Agriculture, 2016)
Agriculture is one of the most vulnerable and adaptation-prone sources of livelihood facing climate change. Joint adaptation planning by far mers and researchers can help develop practically feasible and environ mentally and economically sound adaptation actions as well as encourag e the proactive building of farm adaptive capacity. Here, the percepti ons of Finnish farmers and rural stakeholders regarding intercropping, the cultivation of two or more crop genotypes together in time and sp ace, as a means to prepare for climate change, were collected in an op en workshop. Our aim was to identify the potentials and challenges ass ociated with intercropping, its role as an adaptation strategy, and in farm adaptive capacity. Qualitative analysis revealed better yield se curity, increased nutrient and protein self-sufficiency, soil conserva tion and maintenance, reduced pathogen pressure and regulation of wate r dynamics as the main perceived potentials of intercropping. Potentia ls relating to the farm economy and environment were also recognized. The main challenges associated with intercropping were related to the lack of information on crop variety performance and optimal yielding i n mixtures, industry and policy requirements for seed purity, more com plicated crop management and harvesting, and the economic risks associ ated with experimenting with novel mixtures. Nitrogen-fixing legumes; deep-rooted species, such as lucerne (Medicago sativa L.); special cro ps, such as herbs in forage mixtures; and autumn-sown winter oilseeds and cereals were highlighted as the most promising intercrops. Because the recognized potentials relate to the safeguarding of field croppin g from anticipated climate change and the associated weather variabili ty, we conclude that intercropping can serve as one adaptation strateg y to strengthen the adaptive capacity of Finnish farms. However, assur ing markets and policies that allow the development of intercropping, performing experiments to assess the benefits and implement options in practice, and providing farmers and farm advisors with more knowledge on the method represent the critical prerequisites for the broader ad option of intercropping.
Keywords: Adaptation planning; Adaptive capacity; Climate change; ecological intensification; intercropping; yield security